An unexpected negative feedback between climate change and eutrophication: higher temperatures increase denitrification and buffer nitrogen loads in the Po River (Northern Italy). (1st August 2022) - Gervasio, Maria Pia; Soana, Elisa; Granata, Tommaso; Colombo, Daniela; Castaldelli, Giuseppe
Abstract: Temperature is one of the most fundamental drivers governing microbial nitrogen (N) dynamics in rivers; however, the effect of climate change-induced warming on N processing has not been sufficiently addressed. Here, annual, and seasonal (spring and summer) N loads exported from the Po River watershed (Northern Italy), a worldwide hotspot of eutrophication and nitrate pollution, are investigated in relation to water temperature trends over the last three decades (1992–2019). Despite large inter-annual variations, from the early 1990s, the Po River experienced a significant reduction in total N loads (−30%) represented mainly by nitrate, although agricultural N surplus in croplands and other watershed conditions have remained constant. In parallel, the Po River water is steadily warming (+0.11 °C yr −1, for average annual temperature) and the number of warm days is increasing (+50%, in the spring–summer period). The inverse relationship between water temperature and N loads strongly indicated that the higher temperatures have boosted the denitrification capacity of river sediments along the lowland reaches. Overall, over the last three decades, annual total N loads declined by around one-third due to a near 3 °C increase in temperature and this evidence was even more marked for the summer season (−45% for total N loads and +3.5 °C for temperature). Based on these observations, it is suggested that near-term effects of climate change, i.e. warming and an increase in the duration of low-flow periods in rivers, may have negative feedback on eutrophication, contributing to partially buffer the N export during the most sensitive period for eutrophication.